Comprehensive Parameter Screening for the Investigation of Particulate Fouling in Pipe Fittings. Issue 5 (1st March 2023) - Jarmatz, Niklas; Augustin, Wolfgang; Scholl, Stephan
Abstract: A prominent example of unwanted accumulation in production plants is particulate fouling, which has been subject of many studies in apparatuses. However, pipe fittings have attracted little attention despite their large number in production plants. Here, the influence of process parameters and geometry factors on the fouling in pipe fittings is investigated under isothermal conditions that aims to an improved understanding of their fouling behavior. The variation of fitting type and size, the run time and particle mass fraction have the greatest impact on the fouling mass while the temperature does not influence the result. Abstract : Experimental generation of screening data for fouling in pipe fittings. The experiments are performed under a wide range of process parameters applying a particulate substance system in pipe fittings that exhibit a set of different geometries, orientations and sizes, which leads to highly reproducible results.